2024
DOI: 10.1002/1873-3468.14806
|View full text |Cite
|
Sign up to set email alerts
|

MATR3 pathogenic variants differentially impair its cryptic splicing repression function

Mashiat Khan,
Xiao Xiao Lily Chen,
Michelle Dias
et al.

Abstract: Matrin‐3 (MATR3) is an RNA‐binding protein implicated in neurodegenerative and neurodevelopmental diseases. However, little is known regarding the role of MATR3 in cryptic splicing within the context of functional genes and how disease‐associated variants impact this function. We show that loss of MATR3 leads to cryptic exon inclusion in many transcripts. We reveal that ALS‐linked S85C pathogenic variant reduces MATR3 solubility but does not impair RNA binding. In parallel, we report a novel neurodevelopmental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…More strikingly, MATR3 depletion led to a decrease in the formation of DNA damage-induced RAD51 foci and negatively impacted DNA repair by HR [ 14 ]. MATR3 has also been shown to regulate the levels of RAD17 and UHRF2 [ 16 , 46 ], which have both been shown to have roles in DDR [ 47 , 48 , 49 , 50 ].…”
Section: Matr3’s Role In Dna-related Processesmentioning
confidence: 99%
See 4 more Smart Citations
“…More strikingly, MATR3 depletion led to a decrease in the formation of DNA damage-induced RAD51 foci and negatively impacted DNA repair by HR [ 14 ]. MATR3 has also been shown to regulate the levels of RAD17 and UHRF2 [ 16 , 46 ], which have both been shown to have roles in DDR [ 47 , 48 , 49 , 50 ].…”
Section: Matr3’s Role In Dna-related Processesmentioning
confidence: 99%
“…Many reports have shown that MATR3 interacts with a variety of proteins that are known to function in splicing regulation [ 15 , 33 , 46 , 61 ]. Several studies have shown that the major role of MATR3 is a repressor of exon inclusion [ 15 , 16 , 17 , 19 ]. MATR3’s splicing function is dependent on its RRM domains, while the ZnF domains are largely dispensable [ 15 ].…”
Section: Matr3’s Role In Rna-related Processesmentioning
confidence: 99%
See 3 more Smart Citations